Design, synthesis, and antiproliferative activity of new 1H-pyrrolo[3,2-c]pyridine derivatives against melanoma cell lines. Part 2 - Jung, Myung-Ho; El-Gamal, Mohammed I.; Abdel-Maksoud, Mohammed S.; Sim, Taebo; Yoo, Kyung Ho; Oh, Chang-Hyun (Pergamon Press Ltd., 2012)
A new series of diarylureas and diarylamides possessing 1H- pyrrolo[3,2-c]pyridine scaffold was designed and synthesized. Their in vitro antiproliferative activities against A375P human melanoma cell line and NCI-9 human melanoma cell line panel were tested. All the target compounds, except three amino derivatives 8g, h and 9h, demonstrated superior potencies against A375P to Sorafenib. In addition, compounds 8a and 9b-f demonstrated higher potencies than Vemurafenib against A375P. Compounds 8c and 9b were 7.50 and 454.90 times, respectively, more selective towards A375P melanoma cells over NIH3T3 fibroblasts. Furthermore, compounds 8d, e and 9a-d, f demonstrated very high potencies against the nine tested melanoma cell lines at the NCI. The bisamide derivatives 9a-c, f showed 2-digit nanomolar IC50 values over different cell lines of the NCI-9 melanoma cell lines. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: DIARYLAMIDES; DIARYLUREAS; SORAFENIB; DIAGNOSIS; THERAPY